PENGEMBANGAN VIDEO TUTORIAL PEMBUATAN TAS MAKRAME PADA PEMBELAJARAN KREAVITAS, INOVASI DAN WIRAUSAHAAN SISWA DESAIN DAN PRODUKSI BUSANA KELAS XI SMK NEGERI 1 BUNGO - Dewarni Nasution; Ilham Zamil; Weni Nelmira; Adriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to (1) describe the development process, (2) determine the validity, and (3) determine the practicality of a makrame-bag-making tutorial video for the Creativity, Innovation, and Entrepreneurship subject among eleventh-grade Fashion Design and Production students at SMK Negeri 1 Bungo. The problem addressed is that the video tutorials teachers currently use are general, not designed according to the curriculum and lesson plan, and do not present the knot-tying steps in a detailed and systematic manner, so students still struggle to follow the practice independently. This research and development (R&D) study adapted the 4D model (Define, Design, Develop, Disseminate) by Thiagarajan, limited to the Define, Design, and Develop stages. Data were collected through interviews, observation, and validation and practicality questionnaires administered to media, material, and language experts, one subject teacher, and students in small- and large-group trials. The results show that the developed video tutorial obtained an average validity score of 95% (Very Valid), consisting of 97% from the media expert, 91% from the material expert, and 97% from the language expert. The practicality test results reached 98% from the teacher, 89% from the small-group trial, and 91% from the large-group trial, all in the Very Practical category. These findings indicate that the video tutorial is valid and practical for use as a learning medium in the Creativity, Innovation, and Entrepreneurship subject.